Nanofibrous membranes as smart wound dressings that release antibiotics when an injury is infected - Rivero, G.; Meuter, M.; Pepe, A.; Guevara, M. G.; Boccaccini, Aldo R.; Abraham, G. A. (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2020)
Simple and coaxial electrospinning were used for the preparation of nanofibers containing antibiotic. The use of a pH-sensitive polymer provided the membranes with a selective releasing capability, as a function of the environmental pH. Considering that pH increases as a consequence of local wound infection, the acidity changes of the wound could act as a trigger for the onset of antibiotic treatment in an autonomous way. In this work, electrospun membranes capable of releasing nitrofurazone when there is a change in the acidity of the environment were designed and prepared. The electrospun nanomaterials were fabricated with polymers with selective solubility at pH values greater than 7 so that the active agent is released only in this condition. The use of these membranes as wound dressings would selectively trigger an antibiotic treatment according to the physiological pH of the wound, i.e. only when there are natural signs of infection. The behavior of the membranes was exhaustively studied in different pH media, as well as the membranes integrity and morphology. The nitrofurazone release profiles were measured in-vitro and the antibiotic capability was tested against bacteria.These pH-sensitive nanofibrous drug delivery carriers are proposed as smart wound dressings with remarkable potential for enlarging the therapeutic benefits during medical treatments, according to the physiological conditions of the damaged skin tissues, especially for burns or chronic wounds.
CRIS-Team Scopus Importer:2019-12-20
Keywords: Electrospinning; Nanofibrous membranes; pH-sensitive; Smart wound dressings